1985
DOI: 10.1002/1097-0142(19850815)56:4<758::aid-cncr2820560410>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple daily fractionated radiation therapy and misonidazole in the management of malignant astrocytoma. A preliminary report

Abstract: Various attempts have been made to improve the effectiveness of radiation in the treatment of cerebral malignant astrocytomas. A trend favoring multiple daily fractionated (MDF) radiation therapy over conventional single daily fractionated (CF) radiation therapy was identified in our previous study. In order to assess the effect of MDF with and without misonidazole, a province-wide prospective randomized trial was initiated in January 1981. By March 1984, 124 patients with histologically verified grade III and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…As previously reported [18,19] there was no difference in time to tumor progression or survival between patients on the 6141cGy arm who received misonidazole and those who did not. Therefore, these patients are grouped together in this report.…”
Section: All Patientssupporting
confidence: 83%
“…As previously reported [18,19] there was no difference in time to tumor progression or survival between patients on the 6141cGy arm who received misonidazole and those who did not. Therefore, these patients are grouped together in this report.…”
Section: All Patientssupporting
confidence: 83%
“…In general, no improvement in survival over conventional treatment was seen. In one study a significant advantage to multiple daily fractions was reported (Shin et al, 1985) but the MST in the control group was only 27 weeks, placing the overall conclusion in some doubt.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the trend seen in their previous trial, Shin [29] et al initiated a larger trial of accelerated RT. A total of 124 patients with malignant glioma were randomized to either conventional fractionated RT (40 Gy/20 fractions in 4 weeks to the whole brain with 2 Gy /fraction, followed by a local tumor boost of 20 Gy/10 fractions/2 weeks); or accelerated RT whereby the patients received 0.89 Gy/fraction; 3 fractions/day as whole-brain radiotherapy (WBRT) to a dose of 50.7 Gy/54 fractions in 3.5 weeks followed by a local tumor boost of 10 Gy/5 fractions in 1 week; or to accelerated RT as above plus misonidazole 1.25 gm/m 2 thrice weekly during the first three weeks of radiotherapy.…”
Section: Literature Search Strategy Gymentioning
confidence: 81%
“…The seven randomized studies (Table II) however are not consistent with each other, with the four larger trials [26,27,32,33] reporting no benefit and the two smaller ones [28,31] showing a trend towards improved survival with acceleration over conventional fractionation. Only one study, by Shin et al [29] reported a survival benefit with accelerated RT. However, the number of patients in their study was small (124 patients only) and only the preliminary results were published.…”
Section: Discussionmentioning
confidence: 99%